Co-pyrolysis of pig manure and magnesium-containing waste residue and phosphorus recovery for planting feed corn. (October 2022) - He, Lintong; Wang, Dehan; Wu, Zhaoyun; Li, Sicheng; Lv, Yongzhen
Abstract: South China region took the lead in revising the discharge limit of total phosphorus in livestock and poultry breeding wastewater, reducing the limit from 8 to 1 mg/L. Therefore, the advanced treatment of phosphorus in swine wastewater will become an increasingly important topic. In this paper, magnesium-modified biochar was prepared by co-pyrolysis using pig manure (PM) as raw material and magnesium-containing desulfurization waste residue (MDWR) from a power plant as magnesium salt, which was used to recover phosphorus from pig farm wastewater, and the phosphorus recovery product was used as phosphorus fertilizer in planting feed corn. When the mass ratio of MDWR to PM was 3:10, pyrolysis temperature was 800°C, B@Mg-16 dosage was 1 g/L and initial pH value was 9.0, the phosphorus adsorption capacity of magnesium-modified biochar B@Mg-16 reached 49.37 mg/g, which was 3.51 times that of biochar B-4, and achieved a maximum adsorption of 117.78 mg P/g. Besides, phosphorus-rich magnesium-modified biochar P-B@Mg-16 increased the feed maize crude protein content. The results were of great significance for promoting the integration of crop-livestock production systems and the development of ecological agriculture. Graphical abstract: Unlabelled Image Highlights: Using desulfurized magnesium residue and pig dung to prepare biochar. B@Mg-16 biochar adsorbed up to 117.78 mg P/g. P-B@Mg-16 had a better feed corn yield and crude protein content than SSP fertilizer.